Text cryptography and steganography based on RNA sequences generation, true random number generators, and codebook method - Safwat Hamad; Omar Fitian Rashid; Hind M. Al-Dabbas (PLoS ONE, 2025)
Classic security methods are becoming vulnerable because of technology advancements. The process of combining cryptography and steganography led to overcoming this, where this combination will save the information from potential attackers. This paper proposed a new text security method by combining the cryptography technique and steganography technique, where cryptography is used to encode the message, while steganography is used to hide the ciphertext within an image. The proposed cryptography system has five steps. The first is done by building an RNA sequences generation table to convert the message to RNA sequences, the next step is done by creating a table to convert RNA sequences to decimal numbers. In the third step, the achieved decimal values are converted to binary numbers; after that, used True Random Number Generators method generates the key, and finally, an XOR operation is applied between achieved binary numbers and the generated key. The results achieved by the XOR operation are considered as the ciphertext. Two steps to the proposed steganography method. The first step is done by building a codebook table to select the part of the pixel to store the bit inside it, where the selection part can be either red, green, or blue, and then used a least significant bit to store the bit with no effects on the image. The proposed method presents an efficient solution to secure data, and this method can be applied in different fields, such as information security and privacy protection.